Fluid Inclusion Study of Epithermal Quartz Veins from the Kyaukmyet Prospect, Monywa Copper-Gold Ore Field, Central Myanmar - Toe Naing Oo; Agung Harijoko; Lucas Donny Setijadji (UIR PRESS, 2021)
The Kyaukmyet prospect is located near the main ore bodies of the Kyisintaung and Sabetaung high-sulfidation Cu-Au deposits, Monywa copper-gold ore field, central Myanmar. Lithologic units in the research area are of mainly rhyolite lava, lapilli tuff and silicified sandstone, mudstone and siltstone units of Magyigon Formation which hosted to be polymetallic mineralization. Our field study recorded that epithermal quartz veins are hosted largely in rhyolite lava and lapilli tuff units. Those quartz veins show crustiform, banded (colloform), lattice bladed texture and comb quartz. The main objectives of the present research in which fluid inclusion studies were considered to conduct the nature, characteristics and hydrothermal fluids evolution from the epithermal quartz veins. In this research, there are three main types of fluid inclusions are classified according to their phase relationship (1) two-phase liquid-rich inclusions, (2) the coexisting liquid-rich and vapor-rich inclusions, and (3) only vapor-rich inclusions. Microthermometric measurements of fluid inclusions yielded homogenization temperatures (Th) of 148–282 °C and final ice-melting temperature (Tm) of -0.2°C to -1.4°C . The value of (Tm) are equal to the salinities reaching up 0.35 to 2.07 wt % NaCl equiv. respectively. Estimation formation temperature of the quartz veins provide 190°C and 210°C and paleo-depth of formation are estimated to be between 130m and 210m. Petrography of fluid inclusion and microthermometric data suggest that fluid boiling as well as mixing processes were likely to be happened during the hydrothermal fluid evolution at the Kyaukmyet prospect. According to the characteristics of many parameters including petrography of fluid inclusion, microthermometric data, paleo-depth, evidence of quartz vein textures and types of hydrothermal alteration from the Kyaukmyet prospect allows to interpret these data to be the low-sulfidation epithermal system.